Genre et engagement dans la Résistance : l’exemple d’Anne-Marie Walters - Guillaume Pollack (Genre & Histoire)
During the Second World War, a few women were parachuted into France to fight against nazism. Many of them were arrested and killed in the concentration camps. This episode fascinated English people and many books that told their stories were written in England. However, in France, the fight of these English women during the war is less known than in England. Therefore, this paper proposes to analyse the fight of one of these women, Anne-Marie Walters, in the Wheelwright circuit. The circuit was created by the Special Operation Executives, a secret service set up by Churchill at the beginning of the war in July 1940 « to set Europe ablaze ». Anne-Marie Walters was trained to kill then parachuted in France on January 1944. In the field, she was the courrier of George Starr, the leader of the Wheelwright circuit. Did the enlistment in a circuit imply a gender transgression ?